Anaesthesia apparatus : inter-departmental correspondence - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
041-0028-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From DR. H.B. MORGAN. Department Social Insurance. To MR. W.J. BOLTON. Date 16th April, 1937 SUBJECT. ANAESTHESIA APPARATUS. I was surprised to hear from you that the Trade Union officials in France had been medically advised that the Boyle Apparatus for anaesthesia, about which I submitted some notes and a recommendation, have been unfavourably commented on by their medical advisers. It is an apparatus in common use in hospitals in this country, and giving very good results. It would not, of course, be applicable for work in Field Hospitals, but at Base Hospitals such a piece of apparatus for anaesthesia would be invaluable. I have been advised, too, that this apparatus is best manufactured in England, and the proof of this is to be found in the fact that for the Paris Exhibition the French manufacturers have had to borrow specimens of this apparatus from English manufacturers for exhibition in Paris. My authority for this statement is Mr. Taylor of Down Brothers. Down Brothers is a firm which supplies at least six of the largest and best hospitals in London. I have also made enquiries from the Anaesthestic Section of the Royal Society of Medicine, and my information there tends to confirm this opinion. I do not know on what grounds the medical advisers on the Continent have made their unfavourable comments, but it would be very interesting to have their considered view. H.B. Morgan 292/946/41/28